The Influence of the Solid Earth on the Contribution of Marine Sections of the Antarctic Ice Sheet to Future Sea‐Level Change. Issue 15 (5th August 2022) - Yousefi, M.; Wan, J.; Pan, L.; Gomez, N.; Latychev, K.; Mitrovica, J. X.; Pollard, D.; DeConto, R. M.
Abstract: Seismic tomography models indicate highly variable Earth structure beneath Antarctica with anomalously low shallow mantle viscosities below West Antarctica. An improved projection of the contribution of the Antarctic Ice Sheet to sea‐level change requires consideration of this complexity to precisely account for water expelled into the ocean from uplifting marine sectors. Here we build a high‐resolution 3‐D viscoelastic structure model based on recent inferences of seismic velocity heterogeneity below the continent. The model serves as input to a global‐scale sea‐level model that we use to investigate the influence of solid Earth deformation in Antarctica on future global mean sea‐level (GMSL) rise. Our calculations are based on a suite of ice mass projections generated with a range of climate forcings and suggest that water expulsion from the rebounding marine basins contributes 4%–16% and 7%–14% to the projected GMSL change at 2100 and 2500, respectively. Plain Language Summary: Most of vulnerable sections of the Antarctic Ice Sheet rests on top of bedrock below sea level and the bed deepens inland. Following the ice loss in these sections, the underlying bedrock rebounds and expels the meltwater into the open ocean, a process that is called water expulsion. The impact of this mechanism on future estimates of sea‐level change has not been fully investigated. Here, we project the effect of water expulsion mechanism on geographically variable global sea‐level change. Key Points: We investigate the influence of solid Earth deformation on the contribution of the Antarctic Ice Sheet to projections of sea‐level change The water outflux from uplifting flooded marine basins adds to future projections by up to 16% at the end of the 21st century and 14% at 2500 Not incorporating the 3‐D Earth structure underestimates the geographically variable far‐field sea‐level by up to 20% at the end of the simulations (2500)